A digital image-based traceability tool of the geographical origins of Argentine propolis - Pierini, Gastón Dario (2016)
Propolis is a hive product prepared by honeybees (Apis mellifera L.) widely used in pharmaceutical and food preparationsthat plays beneﬁcial roles beyond basic nutrition and therapeutic properties. These beneﬁts are relatedwith its quality, which depends on various factors, such as geographical origin, botanical sources, collecting seasons,races of honeybees, climatic conditions and also the method of harvest. In this sense, it would be helpful theimplementation of a simple, fast and reliable analytical methodology for quality monitoring of propolis samplesas a traceability tool of its geographical origin. Thus, this work proposes the use of digital images andchemometrics for the classiﬁcation of raw propolis from six different geographical origins of the Buenos AiresProvince, Argentina. For this purpose, different combinations between a color model (Grayscale, RGB and HSI)and a multivariate classiﬁer (PCA?LDA, SIMCA, kNN, PLS-DA and SPA?LDA) were tested. The best analytical performancewas achieved by SPA?LDA using Intensity histograms, classifying correctly a 100% of the samples inboth training and test sets, taking in account the 27 variables selected by SPA. As a consequence, the proposedmethodology serves to support local apiculturists, guaranteeing the offer of products with a clear indication ofgeographical origin, and enhancing regional capabilities.